The paradigm of cytokine networks in allergic airway inflammation. Issue 1 (February 2015) - Pawankar, Ruby; Hayashi, Miyuki; Yamanishi, Shingo; Igarashi, Toru
Abstract : Purpose of review: Cytokines are immunomodulatory proteins important in cell signaling. Complex interactions of innate and adaptive immune cells, as well as structural cells and their cytokines, play crucial roles in regulating allergic airway inflammation. Here, we summarize current knowledge about the potential roles of known and newly identified helper T cells and epithelial cell-derived cytokines [interleukin (IL)-9, IL-17, IL-22, IL-25, and IL-33] in allergic rhinitis and asthma. Recent findings: Although T-helper (Th)2 cells were considered to be the main orchestrators of allergic airway inflammation, recent studies have revealed the potential interaction of other helper T cells and their cytokines in this process. Th17 cells may have a role in allergic rhinitis and asthma, and chronic rhinosinusitis with nasal polyps. An IL-9-producing subset called Th9 cells, Th22 cells which primarily secrete IL-22, IL-13, tumor necrosis factor-α, Th25 cells via producing IL-25 and epithelial cell-derived thymic stromal lymphopoietin, IL-33, IL-31, and IL-25 are believed to be important for the initiation of allergic reactions and inducing airway inflammation. Summary: A new paradigm of an interplay of cytokines is important in allergic rhinitis and asthma in orchestrating the allergic inflammatory response. Potential therapeutic applications emerging from the roles of these cytokines are promising, but need further research.